Genome-wide association study of maternal genetic effects and parent-of-origin effects on food allergy. Issue 9 (March 2018) - Liu, Xin; Hong, Xiumei; Tsai, Hui-Ju; Mestan, Karen K.; Shi, Min; Kefi, Amira; Hao, Ke; Chen, Qi; Wang, Guoying; Caruso, Deanna; Geng, Hua; Gao, Yufeng; et al.
Abstract : Abstract: Previous genetic studies of food allergy (FA) have mainly focused on inherited genotypic effects. The role of parental genotypic effects remains largely unexplored. Leveraging existing genome-wide association study (GWAS) data generated from the Chicago Food Allergy Study, we examined maternal genotypic and parent-of-origin (PO) effects using multinomial likelihood ratio tests in 588 complete and incomplete Caucasian FA trios. We identified 1 single nucleotide polymorphism with significant ( P <  5×10 −8 ) maternal effect on any FA (rs4235235), which is located in a noncoding RNA (LOC101927947) with unknown function. We also identified 3 suggestive ( P <  5×10 −7 ) loci with maternal genetic effects: 1 for any FA (rs976078, in a gene desert region on 13q31.1) and 2 for egg allergy (rs1343795 and rs4572450, in the ZNF652 gene, where genetic variants have been associated with atopic dermatitis). Three suggestive loci with PO effect were observed: 1 for peanut allergy (rs4896888 in the ADGB gene) and 2 for any FA in boys only (rs1036504 and rs2917750 in the IQCE gene). Findings from this family-based GWAS of FA provided some preliminary evidence on maternal genotypic or PO effects on FA. Additional family-based studies are needed to confirm our findings and gain new insight into maternal and paternal genetic contribution to FA. Abstract : Supplemental Digital Content is available in the text